Rhythmic cueing, dance, resistance training, and Parkinson's disease: A systematic review and meta-analysis - Karpodini, Claire Chrysanthi; Dinas, Petros C.; Angelopoulou, Efthalia; Wyon, Matthew A.; Haas, Aline Nogueira; Bougiesi, Maria; Papageorgiou, Sokratis G.; Koutedakis, Yiannis (Frontiers in Neurology, 2022)
Objectives: The aim of the present systematic review and meta-analysis was to synthesize evidence associated with the functional and clinical effectiveness of rhythm in movement, dance and resistance training on motor and non-motor parameters in Parkinson Disease patients and to provide a comparative perspective not offered by existing systematic reviews. Methodology: Eligibility criteria for selecting studies retained no restrictions in methodological design and included interventions of rhythm and /or dance, and/or resistance training and measurements of motor and non-motor parameters. Animal studies, reviews, editorials, conferences, magazines and grey literature articles were excluded. Two independent investigators searched Cochrane Library, Medline, PubMed and Sports Discuss from the date of their inception until June 1st 2021. The ROBINS-I tool was employed for the non-randomized controlled trials and the updated Risk of Bias 2 tool of Cochrane Library for randomized controlled trials. For meta-analyses the RevMan 5.4.13 software was used. For incompatible for meta-analysis studies, a narrative data synthesis was conducted. Results: The total of 50 studies included in the systematic review, involving 3798 PD participants. Significant effect of movement rhythm training on gait velocity [SMD=0.54, confidence interval (CI)=0.21-0.88, z=3.20, I²=46%, P=0.01], stride length [MD=0.09, CI=0.03-0.15, z=3.08, I²=37%, P=0.01], motor symptoms [MD=-3.94, CI=(-7.47)-(-0.41), z=2.19, I²=7%, P=0.03] and cognition [MD=3.98, CI=1.27-6.68, z=2.88, I²=0%, P= 0.01]. Significant effect of dance training on stride length [MD=0.07, CI=0-0.15, z=1.97, I²=0%, P=0.05], lower extremity function-TUG [MD=-1.26, CI=(-1.77)-(-0.75), z=4.82, I²=0% P=0.01] and motor symptoms [MD=-5.38, CI=(-8.44)-(-2.32), z=3.44, I²=79%, P=0.01]. RT significantly improved lower extremity function-TUG [MD=-1.75, CI=(-3.07)-(-0.44), z=2.61, I²=81%, P=0.01], quality of life [SMD=0.38, CI=(-0.67)-(-0.09), z=2.58, I²=31%, P=0.01], knee flexion [SMD=1.00, CI=0.18-1.82, z=2.40, I²=65%, P=0.02] and leg press [SMD=3.51, CI=1.50-5.52, z=3.42, I²=91%, P=0.01]. Conclusion: Rhythm in movement, dance and resistance training affect positively cardinal symptoms of the disease, with rhythm and resistance training to impact most of them. Future studies should consider a) implementation of exercise protocols based on PD patients’ symptomatology, and b) standardization of test protocols. International Prospective Register of systematic reviews (PROSPERO) (registration number: CRD42020212380).